2007
DOI: 10.2136/sssaj2006.0177
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Clay Content across Boundaries at the Landscape Scale with Electromagnetic Induction

Abstract: Detailed information on soil textural heterogeneity is essential for land management and conservation. It is well known that in individual fields, measurement of the soil's apparent electrical conductivity (ECa) offers an opportunity to map the clay content of soils with free drainage under a humid climate. At the catchment scale, however, units of different land management and differing sampling dates add variation to ECa and constrain the mapping across field boundaries. We analyzed their influence and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 19 publications
3
34
1
1
Order By: Relevance
“…Apparent conductivity has also been used as a surrogate measure of soil water content (Allred et al, 2005;Brevik et al, 2006;Hezarjaribi and Sourell, 2007;Huth and Poulton, 2007;Kachanoski et al, 1988Kachanoski et al, , 1990Khakural et al, 1998;Korsaeth et al, 2008;Mueller et al, 2003;Sheets and Hendrickx, 1995;Tromp-van Meerveld and McDonnell, 2009;Waine et al, 2000), soil texture (Heil and Schmidhalter, 2012;James et al, 2003;Saey et al, 2012a;White et al, 2012); and clay content (Cockx et al, 2009;Harvey and Morgan, 2009;King et al, 2005;Mueller et al, 2003;Sommer et al, 2003;Weller et al, 2007;Wienhold and Doran, 2008;Williams and Hoey, 1987). Electromagnetic induction has been used to assess difference in lithology and mineralogy (Bourgault and Rabenhorst, 2012;Doolittle et al, 2005Doolittle et al, , 2013, soil compaction (Al-Gaadi, 2012; Sudduth et al, 2010); CEC (Korsaeth et al, 2008;Triantafilis et al, 2009;), exchangeable Ca and Mg (McBride et al, 1990), CaCO 3 (Vitharana et al, 2008b); soil pH (Bianchini and Mallarino, 2002;Dunn and Beecher, 2007;Van Meirvenne et al, 2013;Vitharana et al, 2008b;Wienhold and Doran, 2008), soil organic carbon …”
Section: Other Soil Propertiesmentioning
confidence: 99%
“…Apparent conductivity has also been used as a surrogate measure of soil water content (Allred et al, 2005;Brevik et al, 2006;Hezarjaribi and Sourell, 2007;Huth and Poulton, 2007;Kachanoski et al, 1988Kachanoski et al, , 1990Khakural et al, 1998;Korsaeth et al, 2008;Mueller et al, 2003;Sheets and Hendrickx, 1995;Tromp-van Meerveld and McDonnell, 2009;Waine et al, 2000), soil texture (Heil and Schmidhalter, 2012;James et al, 2003;Saey et al, 2012a;White et al, 2012); and clay content (Cockx et al, 2009;Harvey and Morgan, 2009;King et al, 2005;Mueller et al, 2003;Sommer et al, 2003;Weller et al, 2007;Wienhold and Doran, 2008;Williams and Hoey, 1987). Electromagnetic induction has been used to assess difference in lithology and mineralogy (Bourgault and Rabenhorst, 2012;Doolittle et al, 2005Doolittle et al, , 2013, soil compaction (Al-Gaadi, 2012; Sudduth et al, 2010); CEC (Korsaeth et al, 2008;Triantafilis et al, 2009;), exchangeable Ca and Mg (McBride et al, 1990), CaCO 3 (Vitharana et al, 2008b); soil pH (Bianchini and Mallarino, 2002;Dunn and Beecher, 2007;Van Meirvenne et al, 2013;Vitharana et al, 2008b;Wienhold and Doran, 2008), soil organic carbon …”
Section: Other Soil Propertiesmentioning
confidence: 99%
“…Examples of the application of EMI-based ECa measurements include soil salinity (e.g., Doolittle et al, 2001;Heilig et al, 2011), spatial patterns of soil texture (e.g., Abdu et al, 2008;Heil and Schmidhalter, 2012), lateral boundaries between soil types (e.g., Anderson-Cook et al, 2002;James et al, 2003), depth of clay-rich layers (e.g., Saey et al, 2009;Doolittle at al., 1994), clay content (e.g., King et al, 2005;Weller et al, 2007), soil compaction (e.g., Al-Gaadi, 2012;Islam et al, 2014), soil CEC (e.g., Headley et al, 2004;Triantafilis et al, 2009), soil organic carbon (e.g., Martinez et al, 2009;Altdorff et al, 2016), assessment of soil quality (e.g., Johnson et al, 2001;Corwin and Lesch, 2005), detection of buried services (e.g., Won and Huang, 2004;El-Quady et al, 2014), and mapping of active layer thickness in permafrost areas (e.g., Hauck and Kneisel, 2008;Dafflon et al, 2013). ECa measurements are widely used in the context of precision agriculture for, e.g., refining existing soil maps (e.g., Doolittle et al, 2008;Martini et al, 2013), precision farming (e.g., Lück et al, 2009;Scudiero et al, 2015), and harvest zoning (e.g., Frogbrook and Oliver, 2007;Priori et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Schloeder et al (2001) observed that ordinary Kriging and inverse distance weighting were similarly accurate and effective methods, while thin-plate smoothing splines with tension were not. Weller et al (2007) concluded not only that the predications for Kriging were not satisfied by the Kriging method but also that it was as good as any other radial base function interpolation.…”
Section: Introductionmentioning
confidence: 98%